PROGRAMA CUIDANDO DO CUIDADOR - Lourdes Lima Ferreira, Maria de; de Oliveira da Silva, Francisca Maria; Medeiros de C Falcao, Ana Alice F; Ferreira Costa Róseo, Fabianne; de Oliveira Cândido, Aracy (SANARE - Revista de Políticas Públicas, 2015)
-